The effect of hypo sludge to the compressibility of soil - Dungca, Jonathan R. (Animo Repository, 2020)
Hypo sludge, a waste product from paper industries, has had very few known uses and is usually only disposed of in landfills after the production process. On the other hand, inferior grade soils are being treated with commercial additives to improve their characteristics, some of which in return cause harm to the environment in their production. Hypo sludge possesses roughly identical elements found in that of commercial additives which highlight its potential of being a viable substitute to the latter. The study focused on the vertical strain and compressive property of soils; and 6 design mixes were formulated: 100% soil; 5% hypo sludge-95% soil; 10% hypo sludge-90% soil; 15% hypo sludge-85% soil; 20% hypo sludge-80% soil; 5% lime-95% soil. Oedometer tests were conducted to analyze the behavior of the soil when cured with the additive. Results from tests concluded that the 10% hypo sludge and 90% soil mix was the optimum mix ratio to produce the greatest positive change in both parameters considered among the other hypo sludge mixes. An empirical model was also developed which determines the vertical strain of a soil sample given an applied vertical load and percentage of hypo sludge added. Moreover, the mix performed just slightly inferior to the commercial additive, lime, therefore proving that hypo sludge is at par to that of the typical soil additive. As a result, a purpose for this waste material has been discovered. © 2020 GEOMATE International Society.